Advances and Challenges in Cancer Stem Cells for Onco-Therapeutics - Sulaiman Mohammed Alnasser (Hindawi Limited, 2023)
Six decades have passed since the foundational recognition of the primary properties of the stem cells. Research on stem cells has since remained at the forefront of efforts to combat a spectrum of diseases, most notably cancer. Despite remarkable progress in medical science, a definitive cure for cancer has remained elusive, spurring the pursuit of diverse therapeutic strategies, among which stem cell therapy is a particularly promising avenue. Moreover, the utilization of cancer stem cells as a therapeutic source holds immense potential for addressing intractable diseases. The strategy of targeting cancer stem cells is beset with challenges, including immune rejection and disease relapse. Additionally, the capacity to inadvertently generate cancer stem cells upon transplantation underscores the critical need to eliminate these cells to ensure the efficacy of cell-based therapies. This paper underscores the pivotal role of cancer stem cells in onco-therapeutics and their potential to aid in early cancer diagnosis. With the proliferation of tissue banks and their collection of malignant tissue types, a renewable source of medications to combat cancer is on the horizon. While cancer stem cell-based therapy presents sophisticated and significant challenges, it offers unprecedented opportunities to extend human life. Continued technological advancements in stem cell therapy promise to provide new insights and refine approaches for cancer treatment, ushering in a new era of hope and innovation in the fight against this formidable disease.